2014
DOI: 10.2217/cer.14.72
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure to support learning health systems: are we there yet? Innovative solutions and lessons learned from American Recovery and Reinvestment Act CER investments

Abstract: The 11 big health data networks participating in the AcademyHealth Electronic Data Methods Forum represent cutting-edge efforts to harness the power of big health data for research and quality improvement. This paper is a comparative case study based on site visits conducted with a subset of these large infrastructure grants funded through the Recovery Act, in which four key issues emerge that can inform the evolution of learning health systems, including the importance of acknowledging the challenges of scali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…By 2020, the volume of health data generated worldwide is expected to reach 25,000 petabytes, a 50-fold increase from the amount of data generated in 2012 [ 1 ]. The Health Information for Economic and Clinical Health (HITECH) Act [ 2 3 ], the Patient Protection and Affordable Care Act [ 4 ], and the American Recovery and Reinvestment Act [ 5 ] facilitated an unprecedented collection of electronic health data [ 6 7 ] in an effort to improve patient care. As a result of HITECH, the adoption and use of electronic health records (EHRs) [ 3 ] has drastically increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2020, the volume of health data generated worldwide is expected to reach 25,000 petabytes, a 50-fold increase from the amount of data generated in 2012 [ 1 ]. The Health Information for Economic and Clinical Health (HITECH) Act [ 2 3 ], the Patient Protection and Affordable Care Act [ 4 ], and the American Recovery and Reinvestment Act [ 5 ] facilitated an unprecedented collection of electronic health data [ 6 7 ] in an effort to improve patient care. As a result of HITECH, the adoption and use of electronic health records (EHRs) [ 3 ] has drastically increased.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of EHR in data-driven decision making and comparative effectiveness research (CER) faces many challenges including: governance and stakeholder misalignment [ 21 ] and lack of mutually accepted guidelines for data sharing [ 6 22 ], data integration and aggregation [ 23 ], DQ [ 18 24 25 26 27 ], data standards [ 24 ], infrastructure and data management [ 6 21 ], and record linkage [ 18 ]. Further, guidelines for security and privacy [ 6 10 28 ] and analytics and tool development are under-developed [ 21 28 30 ]. The most informative health data (e.g., data stored in EHRs, personal wellness devices, and medical research applications) are not ‘off-the-shelf’ ready for analysis; [ 31 ] these data are subject to different regulations and standards, and often violate fundamental assumptions of DQ [ 26 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of organizations have begun to use the LHS model to organize for learning although application of the model remains largely conceptual. 3 8 Senior leadership support and operational-research partnerships have been identified as key components of successful LHS activity, 9 15 yet little has been published to provide guidance on important operational issues and strategies for systemwide learning and operationalization of the LHS model. 16 18 A recent survey of leaders and managers from organizations involved in patient-centered network programs funded by the Patient-Centered Outcomes Research Institute (PCORI) recognized that research had a beneficial role to play in care delivery, but discussed a number of challenges with integrating research into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of a “learning network” was used to refer to either learning collaboratives or learning systems [ 122 , 123 ]. However, learning networks could also be defined as a method for bringing learning systems together around a common theme such as primary care [ 86 , 124 , 125 ]. There are few studies in the literature on learning networks, in particular on a global scale.…”
Section: Resultsmentioning
confidence: 99%